Experimental investigation of ion production and acceleration mechanism in laser-produced plasma at moderate intensity for nuclear studies @ ELI-NP. (10th April 2017) - Altana, C.; Tudisco, S.; Lanzalone, G.; Mascali, D.; Muoio, A.; Brandi, F.; Cristoforetti, G.; Ferrara, P.; Fulgentini, L.; Koester, P.; Labate, L.; Palla, D.; et al.
Abstract: High-power lasers allow to produce plasmas extremely appealing for the nuclear physics studies. An intense scientific program is under preparation for the experiments that will be conducted at the Extreme Light Infrastructure for Nuclear Physics (ELI-NP) in Magurele, Romania. Among the several planned activities, we aim to study low-energy fusion reactions and nuclear structure in a plasma environment. In this work, we discuss the results of some preliminary tests related to the experimental set-up, which is in phase of preparation, for the conduction of this scientific program at ELI-NP. Tests have been performed at ILIL laboratory in Pisa, where a Terawatt laser is installed. The goal of this experimental campaign was a systematic experimental investigation of ion production and acceleration mechanism that occur in laser-produced plasma at moderate intensity, I = 10 18 –10 22 W/cm 2 . We particularly focus the attention to identify the role of the target composition: surface contaminants versus volume contribution.